Beaver texts, Beaver dialect. Anthropological papers of the AMNH - Goddard, Pliny Earle, 1869-1928. (New York : Published by order of the Trustees [of the American Museum of Natural History], 1917)
1 p. l., p. 295-546. illus. 25 cm.